Genome-wide identification and single-cell transcriptomic analysis of the mcm gene family in zebrafish reveals its role in TCDD-induced reproductive toxicity - Wenbo Jiang; Xinyi Li; Yubo Zhao; Xinyue Yang; Manting Jin; Jiayu Li; Jiayang Zhao; Ying Huang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Atherogenic index of plasma and high-sensitivity C-reactive protein: combined effects on stroke risk in a middle-aged and elderly non-diabetic cohort - Xiaotong Yao; Liting Liang; Jia Chen; Manting Yang; Yanling Liang; Xiaobo Fang (Acta Neurologica Belgica, 2026)

Trace elements in surface sediments along the Shenzhen coast, South China: Spatial-seasonal patterns, ecological risk, and PMF-based source apportionment - Cheng Chen; Ziliang Chen; Pujiang Huang; Liangming Wang; Binbin Shan; Yan Liu; Yingbang Huang; Zaiwang Zhang; Qijian Xie; Manting Liu; Dianrong Sun; Changping Yang (Regional Studies in Marine Science, 2026)

A novel unsupervised algorithm for pig anomaly detection using video frame prediction - Zezhong Chen; Qiumei Yang; Deqin Xiao; Jiyan Wu; Manting Wu; Qiwei Hong (Biosystems Engineering, 2026)

Quantifying behavioural patterns for group-housed pigs based on deep learning and statistical analysis - Jiyan Wu; Qiumei Yang; Deqin Xiao; Manting Wu; Zezhong Chen; Qiwei Hong (Computers and Electronics in Agriculture, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Associations of long-term exposure to fine particulate matter and its components with ovarian aging: Evidence from a cross-sectional study in China - Zifeng Cao; Xinyi Wu; Hongyuan Liu; Keyan Xu; Yehuan Yang; Manting Yang; Daimin Wei; Shidou Zhao; Xue Jiao; Qi Zhao; Ruimin Zheng; Yingying Qin; et al. (Journal of Hazardous Materials, 2025)

Multi-sites coupled catalyst monolith for flexible/self-driving electrochemical powers and smart strain sensors - Yuankun Liang; Ming Yi; Shiyao Xiang; Kunlong Zheng; Manting Cai; Qiongzhi Gao; Qing Wen; Siyuan Yang; Shengsen Zhang; Yueping Fang; Xin Cai (Chemical Engineering Journal, 2025)

Microsatellite-Marker-Based Evaluation of Stock Enhancement for Kuruma Prawn Penaeus japonicus in Beibu Gulf, South China Sea - Mengyi Zhang; Yu Zhao; Binbin Shan; Yan Liu; Changping Yang; Liangming Wang; Manting Liu; Qijian Xie; Yuan Li; Jianwei Zou; Dianrong Sun (Fishes, 2023)
The objectives of this study were to evaluate the effect of stock enhancement on Penaeus japonicus (Bate, 1888) in Beibu Gulf, South China Sea, and to investigate whether stock enhancement has genetically affected the natural population of P. japonicus in the Beibu Gulf waters. Five microsatellite loci were used to identify released individuals among recaptured specimens. In total, 13 of the 487 recaptured individuals were found with their corresponding parents for this release of shrimp seedlings, accounting for 2.67% of the total recaptured P. japonicus. Furthermore, it was determined that the genetic differences among the broodstock, released, and recaptured populations of P. japonicus were small and did not cause significant changes in the genetic structure of P. japonicus in the area. In conclusion, the stock enhancement of P. japonicus in Beibu Gulf had a certain effect on resource restoration, and there is no difference in the genetic characteristics obtained by the microsatellite markers compared to the original population in this area.

Ecological Niche and Interspecific Association of the Main Fishes in the Coastal Waters of Hainan Island, China - Zhengli Luo; Yanbo Zhou; Ning Liu; Liangming Wang; Yan Liu; Binbin Shan; Manting Liu; Cheng Chen; Changping Yang; Dianrong Sun (Fishes, 2023)
This study explored the ecological niche and interspecific relationships among the main fish species in the coastal waters of Hainan Island based on data from fishery stock surveys conducted in the spring and autumn of 2022. The methods of chi-square test, percentage of co-occurrence (PC), association coefficient (AC), cluster analysis, and redundancy analysis were used to analyze the interspecific associations and influence of environmental factors on the ecological niches of fish communities. According to the cluster analysis of niche breadth, 20 main fishes could be divided into broad, medium, and narrow niche species. There were four and eight broad niche species in spring and autumn, respectively. The ranges of niche overlap values were 0.001–0.91 in spring and 0–0.87 in autumn, indicating that the species differed and were similar in their ability to utilize resources, survive in habitats, and prey. According to the variance ratio and statistic value W, the main fishes in spring showed a significant positive association, whereas those in autumn showed a positive association, but not at a significant level, indicating that the main fishes in spring were more closely associated with each other. There were 56 species pairs in the 2 seasons that were significantly associated (χ2 ≥ 3.841). AC and PC tests revealed that the interspecific association was strong and tended to be positive. According to the redundancy analysis, environmental factors such as surface temperature, water depth, and pH significantly affected the main fishes in spring, while environmental factors such as dissolved oxygen, bottom temperature, surface salinity, and pH significantly affected those in autumn.

Identifying oxidative stress-related biomarkers in idiopathic pulmonary fibrosis in the context of predictive, preventive, and personalized medicine using integrative omics approaches and machine-learning strategies - Fan Yang; Wendusubilige; Jingwei Kong; Yuhan Zong; Manting Wang; Chuanqing Jing; Zhaotian Ma; Wanyang Li; Renshuang Cao; Shuwen Jing; Jie Gao; Wenxin Li; et al. (EPMA Journal, 2023)

Sulfate reduction behavior in pressure-bearing leachate saturated zone - Dongsheng Shen; Haomin Zhou; Zhiyuan Jin; Wenyi Yang; Manting Ci; Yuyang Long; Lifang Hu (Journal of Environmental Sciences, 2023)